An Analysis Of Hyper Boleon Jokowi Speech - Nurhusnaini, Mita (Universitas Muhammadiyah Sumatera Utara, 2021)
The aim of the study is to investigate the meaning of hyperbole expression and todescribe the realization of hyperbola expression on the Jokowi political speech.Descriptive qualitative research was applied this study. The data that used in thisresearch was the transripct of Jokowi?s political speech (Jokowis Political SpeechatA PECCEOSUMMIT 2014, Asian-African Conference Commemoration(AACC) 2015, Indonesian Presidential Election 2019, and General Debate of the75th Session United Nations General Assembly 2020). The source of data were taken from website Cabinet Secretariat ofthe Republic of Indonesia. From the data analysis, it was found 12 expressions used hyperbole in the Jokowi transcript speech. 4 hyperboles in APECCEOSUMMIT 2014, 4 hyperboles in Asian-African Conference Commemoration (AACC) 2015, 3 hyperboles in Indonesian Presidential Election 2019, and 1 hyperbole in General Debate of the 75th Session United Nations General Assembly 2020. The meaning of each hyperbole have adifferent meaning for different purposes. The hyperbole can be realized through 3 type sofword classes usedas word choices.3 hyperboles as adjective,5 hyper boles as noun, and 4 hyper boleas verb.